Effect Of Stand-Off Distance And Plasma Current On The Properties Of Hydroxyapatite Coatings Produced By Plasma Spray - Sulaiman, Wan Ruzaini Wan (2014)
Plasma sprayed hydroxyapatite (HA) coatings on metallic implants for biomedical applications are attracted significant researchers interest due to accelerated rate of bone bonding that occurs following their implantation. This present work aims to produce plasma sprayed HA coatings with varying spray parameters (i.e.; stand-off distance, SOD and plasma current, PC) in order to control the coatings crystallinity. The substrate used is 316L stainless steel. Five SODs were selected i.e. 80 mm, 100 mm, 120 mm, 140 mm and 160 mm combined with two different PCs (500 A and 600 A), respectively. The coatings then divided into two groups (as sprayed and heat treated). Both coating was subjected to in vitro test through immersion in SBF solution up to 28 days to determine their bioactivity. The coating properties before and after immersion in SBF were analyzed using FESEM and XRD. The analysis showed coatings morphology consists of type III, V and VIII splats with lamella and non-lamella structures. The crystallinity of as-sprayed coatings is in vicinity of 50%. However, the crystallinity increases more than 90% after heat treatment process. The in vitro analysis proved that the highest apatite layer precipitations on surface with coatings surface was from the assprayed coatings rather than the one being heat treated. Therefore, the quality of HA coating via plasma spray coating technique can be modified through the suitable combination is at SOD 120 mm and PC 600 A.